Changes in the Spatial Concentration of Employment across US Counties: A Sectoral Analysis 1972-2000. - Desmet, K; Fafchamps, M (2005)
Using US county data, we estimate employment growth equations to analyze how the spatial distribution of jobs has changed between 1972 and 2000. We find that total employment has become increasingly concentrated. This aggregate picture hides important sectoral differences though: whereas non-service employment has been spreading out, service jobs have clustered in areas of high aggregate employment. By controlling for employment at different distances, we explicitly take into account the spatial dimension. This allows us to conclude that the spreading out of non-service jobs has benefitted counties 20 to 70 km away from large agglomerations, whereas the concentration of services has come at the expense of jobs in the surrounding 20 kilometers.